Aspek Perancangan Sistem Listrik Hybrid - Fikri, Muhammad Jubbari; Yasri, Indra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The reliability of power supply from electricity from national electrical company still remain an issue in certain big cities. This issue is contributed by many root caused such as lack of electrical generator, human error, disaster and others. Due to this, it is urgent to deploy a hybrid electricity. This purpose a hybrid control system to ensure continuity of electricity supply. This control system is designed to accomodate multiple electrical sources which is available such as wind turbine, solar panel and diesel generator. The main priority source to supply the load still electricity from national company because it has the most reliable power. This automatic transfer system is based on ATMega8535 microcontroller. This automatic transfer system is used to backup power that have to reliable and uninterrupted. Parameters which are influence to this design aspect are described.Keyword : ATMega8535, automatic transfer switch, Hybrid control system